LB17. Age-Related Differences in Influenza Type/Subtype Among Patients Hospitalized with Influenza, FluSurv-NET—2017–2018. (26th November 2018) - Garg, Shikha; O'Halloran, Alissa; Cummings, Charisse Nitura; Anderson, Evan J; Alden, Nisha; Bennett, Nancy M; Billing, Laurie; Chai, Shua J; Kim, Sue; Lynfield, Ruth; Muse, Alison; Price, Andrea; et al.
Abstract: Background: The 2017–2018 influenza season had the highest rates of influenza hospitalizations since the 2009 H1N1 pandemic. We used data from the Influenza Hospitalization Surveillance Network (FluSurv-NET) to identify unique characteristics of the 2017–2018 season. Methods: We included all patients residing within a FluSurv-NET catchment area, and hospitalized with laboratory-confirmed influenza during 2017–2018. We used multiple imputation, including age, surveillance site, and month of hospital admission as predictors, to impute influenza A subtype for 40–64% of cases across seasons with an unknown subtype. We calculated influenza hospitalization rates by type/subtype per 100, 000 population. We compared 2017–2018 rates to rates during 4 prior seasons: 2016–2017, 2015–2016, 2014–2015, and 2013–2014. Results: The overall unadjusted hospitalization rates per 100, 000 population varied from 31.5 during 2015–2016 to 105.1 during 2017–2018. After imputing A subtype, the 2017–2018 season had the highest rates observed for H3N2 (62.8) and B (28.5) than in any previous season, and the third highest rate of H1N1 (13.5) (Figure 1A). During 2017–2018, rates in adult ≥65 years peaked 3 weeks before they peaked in children 0–4 years. In contrast, during the four prior seasons, rates in adults ≥65 years peaked during the same week or 1 week after they peaked in children 0–4 years. During 2017–2018, the distribution of influenza type/subtypes varied significantly by age group ( P < 0.0001); for example, the proportion of cases with H1N1 ranged from 19 to 29% in those <65 years to only 7% in those ≥65 years. During 2017–2018, H1N1 (the nonpredominant A virus) contributed >25% of A cases across all age groups (except ≥65 years) vs. all prior seasons where the nonpredominant A virus contributed <10% of A cases across all age groups (except ≥65 years) (Figure 1B–F). Conclusions: Several unique characteristics may have contributed to the high hospitalization rates observed during 2017–2018. Rates in older adults, who were predominantly infected with H3N2, peaked several weeks prior to children in contrast to prior seasons. Higher overall rates of H3N2 and B were observed in 2017–2018 compared with these prior seasons and substantial H1N1 co-circulation also occurred with marked variability by age group. Disclosures: E. J. Anderson, NovaVax: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. AbbVie: Consultant, Consulting fee. MedImmune: Investigator, Research support. PaxVax: Investigator, Research support. Micron: Investigator, Research support. H. K. Talbot, Sanofi Pasteur: Investigator, Research grant. Gilead: Investigator, Research grant. MedImmune: Investigator, Research grant. Vaxinnate: Safety Board, none. Seqirus: Safety Board, none.